The criteria and potential adaptive reuse of pre-war shophouses - Mohd Abdullah, Muhamad Shahril (2018)
Pre-war shophouses in some town areas of Malaysia are among national heritage buildings which require conservation efforts, among other through adaptive reuse. Adaptive reuse, in line with sustainability principles, is a process to revitalise or reinvent disused or ineffective existing buildings including old or historical buildings for new use, purpose or function. The aim of this study is to propose the decisionmaking in selecting the optimal reuse of pre-war shophouses by considering the importance criteria that are influenced the adaptive reuse process. A questionnaire survey among four (4) selective respondents consist of town planner from local authorities, valuer from valuation and property service department (JPPH), architects and building owners conducted to achieve the objectives. From the analysis, five (5) potential new uses which are new shophouses, pharmacy hotel, rental house anda restaurant were identified as a very suitable. Thirty-three (33) criteria were classified into six aspects which are economic, environment, social, architecture, technology, and legislative. Out of them, sixteen (16) criteria were identified as very important to be considered in deciding adaptive reuse for pre-war shophouses. The outcome of this study is a conceptual framework that can assist stakeholders, especially local authorities, Valuation and Property Service Department (JPPH), architects and building owners, in adaptive reuse decision-making process. This conceptual framework proposedly can be used by architects as the main actors in adaptive reuse process, building owners since they are the most entitle person to decide any conversion on their buildings, and government bodies since they are involved directly in preparing the guidelines for conservation of pre-war shophouse.